Characteristics of Starch in Argentinean Malting Barley - Lopez, Olivia Valeria (2007)
Sixteen samples of malting barley grown in the Buenos Aires Province of Argentina were selected for this study. Starch was isolated and purified using a modified version of the Morrison method. The starch concentration in the samples ranged from 53.2 to 63.3%. The starch samples were characterized physicochemically, and the following results were obtained: 1) the concentration of lipids, phosphorus, and nitrogen was too low; 2) the values for apparent amylose ranged from 19.0 to 23.9%, whereas the values for total amylose ranged from 23.6 to 31.2; 3) the starch had a bimodal granule size distribution?type A (big and lenticular) and type B(small and irregular or spherical); 4) the gelatinization temperature ranged from 62.18 to 64.68°C; 5) amylopectin was responsible for the crystallinity of starch granules; and 6) the granules were birefringent. The last property disappeared when starch was heated above its gelatinization temperature.